2021
DOI: 10.3389/fimmu.2021.762341
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Adaptive Immune Therapy in MSS Colorectal Cancer Patients

Abstract: Colorectal cancer (CRC) is one of the most common cancers worldwide. However, the treatment outcomes of immunotherapy in microsatellite-stable (MSS) CRC remain unsatisfactory. As the majority of CRC cases display a molecular MSS/mismatch repair-proficient (pMMR) profile, it is particularly meaningful to explore the clinical applications of adaptive immune therapy in MSS CRC patients. In this review, we summarized the therapeutic approaches of adoptive immune therapies, including cytokines, therapeutic cancer v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…However, dMMR/MSI-H CRC comprises approximately 5% of metastatic CRC, and the efficacy of ICIs has been unsatisfactory in the majority of CRC which is mismatch repair proficient (pMMR) or microsatellite stable (MSS) [ 66 , 67 ]. Because MSS metastatic CRC is usually classified as a typical “cold” cancer that presents a lack of the activation of immune responses, the studies investigating how to generate a “hot” TME are critical to the treatment improvement of MSS CRC [ 68 , 69 ]. The production of CXCL9 in the TME can induce T-cell infiltration and may contribute to the orchestration of the “hot” TME of MSS CRC.…”
Section: Discussionmentioning
confidence: 99%
“…However, dMMR/MSI-H CRC comprises approximately 5% of metastatic CRC, and the efficacy of ICIs has been unsatisfactory in the majority of CRC which is mismatch repair proficient (pMMR) or microsatellite stable (MSS) [ 66 , 67 ]. Because MSS metastatic CRC is usually classified as a typical “cold” cancer that presents a lack of the activation of immune responses, the studies investigating how to generate a “hot” TME are critical to the treatment improvement of MSS CRC [ 68 , 69 ]. The production of CXCL9 in the TME can induce T-cell infiltration and may contribute to the orchestration of the “hot” TME of MSS CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the principle of most therapeutic cancer vaccine is based on the establishment of TAA -specific antitumor immune response to eliminate tumor cells expressing these antigens ( 91 ). Cancer vaccines include cell (autologous, DC) vaccines, protein/peptide vaccines, and gene vaccines ( 92 ) ( Figure 1 ). Many studies have identified a variety of TAA expressed by CRC cells as potential targets for vaccine immunotherapy, including CEA, WT1, MUC1, RNF43, GUCY2C, SART3, and hTERT ( 91 ).…”
Section: Cancer Vaccinesmentioning
confidence: 99%
“…For precise tumor targeting, potential solutions can be used, such as targeting T-cells with tandem CARs, universal CARs, affinity tuning, and regulation of CAR expression levels ( 166 ). In addition, preliminary data have provided promising evidence for combination therapies of CAR T-cells and other immunotherapies, chemotherapy, or radiotherapy ( 167 ).…”
Section: Car T-cell Trials In Crcmentioning
confidence: 99%